A new genus and species of Neotropical gregarious braconine parasitoid (Hymenoptera: Braconidae) of a caterpillar (Lepidoptera: Hesperiidae) - Quicke, Donald L.j.; Sharkey, Michael J.; Janzen, Daniel; Hallwachs, Winnie; Hebert, Paul D.n.; Butcher, Buntika A. (Zootaxa, 2020)
A new genus of braconine parasitoid wasp, Acgorium Sharkey & Quicke gen. nov., based on a new species from Costa Rica, Acgorium felipechavarriai Sharkey sp. nov., is described and illustrated, based on specimens reared from wild-caught hesperiid caterpillars of Dyscophellus phraxanor (Hewitson). Acgorium felipechavarriai is the first known braconine gregarious ectoparasitoid of a butterfly caterpillar.